THE APPLICATION OF BENTONE AS NANOFILLER IN POLYPROPYLENE NANOCOMPOSITES - Ariadne L. Juwono; Seto Roseno; Andes T. Agnelia (Jurnal Sains Materi Indonesia, 2011)
THE APPLICATION OF BENTONE AS NANOFILLER IN POLYPROPYLENE NANOCOMPOSITES. For the last two decades, thermoplastic polymer based nanocomposites have been developed because of their superior properties. The benefits of these materials are light weight, high stiffness, and good resistance. With an addition of a small amount of filler, some properties improved significantly. This paper presents the tensile and flexural properties of a polypropylene with a dispersion of commercial Bentone clay in the matrix. Bentone polypropylene nanocomposites were successfully prepared by a melt intercalation method. The melting process was initiated by the addition of a modifier and an initiator. Bentone polypropylene nanocomposites with the variation of bentone contents were then analyzed. A pattern of clay morphology typically found in polypropylene based nanocomposites was observed using an X-Ray diffraction and a transmission electron microscope. These findings showed that an intercalated structure was formed. Furthermore, the value of tensile and flexural modulus as well as the value of tensile strength increased by an addition of 1 wt% bentone.